2016
DOI: 10.1002/cne.23959
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the M2 muscarinic cholinergic receptor in dendrites, cholinergic terminals, and noncholinergic terminals in the rat basolateral amygdala: An ultrastructural analysis

Abstract: Activation of M2 muscarinic receptors (M2Rs) in the rat anterior basolateral nucleus (BLa) is critical for the consolidation of memories of emotionally arousing events. In the present investigation immunocytochemistry at the electron microscopic level was used to determine which structures in the BLa express M2Rs. In addition, dual localization of M2R and the vesicular acetylcholine transporter protein (VAChT), a marker for cholinergic axons, was performed to determine if M2R is an autoreceptor in cholinergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 86 publications
(130 reference statements)
7
20
0
Order By: Relevance
“…2A). M 2 R-ir in the BLa was very dense in the neuropil, but virtually all cell bodies appeared unstained as in previous studies in the rat (McDonald and Mascagni 2011, Muller et al 2016) (Fig. 2B).…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…2A). M 2 R-ir in the BLa was very dense in the neuropil, but virtually all cell bodies appeared unstained as in previous studies in the rat (McDonald and Mascagni 2011, Muller et al 2016) (Fig. 2B).…”
Section: Resultssupporting
confidence: 78%
“…In fact, about three-quarters of the total M 2 R+ immunoparticles in the neuropil of the BLa were contained in dendritic shafts and spines. The prominent expression of M 2 Rs in these dendritic structures was also seen in the rat BLa using immunoperoxidase (IP) techniques, where it was found that over 90% of dendritic shafts and over 50% of dendritic spines were M 2 R+ (Muller et al, 2016). In the rat BLa using the IP technique it was observed that label for M 2 R was sometimes found adjacent to or contacting the plasma membranes of dendrites and spines, including at the edges of cholinergic synapses, suggesting that the excitability of dendrites could be modulated via M 2 Rs (Muller et al, 2016).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations